1995
DOI: 10.1016/0009-9236(95)90022-5
|View full text |Cite
|
Sign up to set email alerts
|

Fosinopril: Pharmacokinetics and pharmacodynamics in congestive heart failure*

Abstract: Fosinoprilat, the active product of fosinopril, is eliminated by a hepatic pathway, in addition to the renal pathway shared by other angiotensin converting enzyme inhibitors. Congestive heart failure (CHF) may elevate drug plasma concentrations caused by a reduction in steady-state volume of distribution (Vss) and/or an impairment of clearance. This study compared the pharmacokinetics and pharmacodynamics of fosinopril (intravenous and oral) in 10 patients with established CHF and 10 age-, sex-, and weight-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Other indices of RAS activity have not been reported. These results were similar to those found for Caucasians, both normal 34 and with heart failure, and in single or steady-state dosing.…”
Section: Fosinoprilsupporting
confidence: 87%
See 1 more Smart Citation
“…Other indices of RAS activity have not been reported. These results were similar to those found for Caucasians, both normal 34 and with heart failure, and in single or steady-state dosing.…”
Section: Fosinoprilsupporting
confidence: 87%
“…33 Fosinopril pharmacokinetics have been studied in 12 healthy Chinese and 10 healthy Caucasians using single 10.0 mg oral doses. 29,34 Data were combined from two studies which used the same methods and analytic techniques (one in Chinese 29 and one in Caucasians 34 ). Plasma concentrations across time (Table 1, rows 5 and 6 and Figure 1b) and renal clearance were similar in Chinese and Caucasians.…”
Section: Fosinoprilmentioning
confidence: 99%
“…It is not possible to establish whether changes in liver and/or renal function might have influenced the results as the relevant information was not provided in this study . By contrast, no significant alterations in the pharmacokinetics of fosinopril and irbesartan were observed in HF .…”
Section: Resultsmentioning
confidence: 84%
“…A total of 59 studies (49 on cardiovascular drugs) investigating 36 drugs (31 cardiovascular) were identified (Tables ). Twelve studies were published in the period 1970–1979 , 20 in the period 1980–1989 , 12 in the period 1990–1999 , 10 in the period 2000–2009 , and five in the period 2010–2018 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, phosphinate and phosphonate derivatives have been explored as transition‐state analogues and inhibitors of therapeutically relevant protease enzymes. Examples include the antihypertension drug fosinoprilat ( 1 , a potent inhibitor of the zinc‐metallopeptidase angiotensin‐converting enzyme; ACE) and preclinical anti‐inflammatory agent 2 (an inhibitor of the human mast cell chymase) . Six‐membered ring phosphinates (known as oxaphosphinanes or phostines) and phosphonates (known as phostones) have also been previously explored in drug discovery as bioisosteres of the furanose or pyranose ring, in which the anomeric carbon atom is replaced by the phosphinate or phosphonate moiety.…”
Section: Introductionmentioning
confidence: 99%